Pengaruh Iklan Tiktok, Kualitas Produk dan Harga terhadap Minat Beli Produk Scarlett Whitening - Julia, Siti; K, Kamilah (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to examine the effect of advertising, product quality and price on buying interest in students of the State Islamic University of North Sumatra, either partially or simultaneously. This study used a quantitative method with data collection using the Likert scale method. The subjects used in this study were 100 students of the State Islamic University of North Sumatra and were taken using purposive sampling. Data analysis techniques through the IBM SPSS statistics 22 program. The results of this study indicate that first, advertising has a positive and significant effect on purchase intention with a significant value of 0.027 <0.05. Second, Product Quality has a positive and significant effect on Purchase Intention with a significant value of 0.000 <0.05. Third, price has a positive and significant effect on buying interest with a significant value of 0.035 <0.05. Advertising, Product Quality and Price simultaneously have a positive and significant effect on Purchase Intention with a significant value of 0.000 <0.05.